Analysis of Factors that Influence Students in Continuing Their Education - Rosnidarwati, Rosnidarwati (Journal La Edusci, 2025)
This study aims to analyze the factors influencing students' decisions to pursue higher education majoring in Islamic Studies. Using a mixed methods explanatory sequential design approach, this study explores five key constructs influencing student choice: family support, personal interest, religious understanding, perceptions of the quality of Islamic educational institutions, and career prospects. Quantitative data were collected through a Likert-type questionnaire and analyzed descriptively, while qualitative data were obtained through structured interviews to strengthen and explain the numerical findings. The study involved 105 students from three Muhammadiyah schools and one non-Muhammadiyah school. The results indicate that students' decisions are not determined by a single factor, but rather the result of an interaction between family values, institutional experiences, and spiritual motivation. Family support emerged as the most dominant factor in shaping students' religious orientation, while personal interest and institutional quality were strengthened by religious experiences at school and teacher role models. Religious understanding became an intrinsic driver for students to systematically deepen their religious knowledge, while career prospects had the least influence because Islamic education was seen more as a path to meaning than as economic considerations. Comparisons between schools indicate that environments with a religious identity, such as Muhammadiyah, foster a greater interest in Islamic studies. These findings confirm that the choice of Islamic studies is a multidimensional process influenced by the configuration of values, school culture, and students' spiritual aspirations.